Incidence of Carcinoma of Gall Bladder Among Patients of Cholelithiasis - Raina, Urooj Mehtab; Ahmed, Gulzar; Javed, Aemun; Fayyaz, Tehwarsham Bin (Indus Journal of Bioscience Research, 2025)
Introduction: Cholelithiasis, gallbladder adenomatous polyps, gallbladder wall calcification, choledochal cysts, and chemical carcinogens are risk factors for gallbladder cancer. Usually discovered by chance, gallbladder cancer is identified by histological analysis after cholecystectomy for cholelithiasis. I have chosen to carry out this investigation in order to ascertain the prevalence of gallbladder cancer in cholelithiasis patients. Study design: Descriptive, cross sectional study. Settings: Department of Surgery, Shahida Islam Teaching Hospital, Lodhran. Study Duration: 23rd July 2024 to 22nd January 2025. Materials & Methods: A total of 370 patients aged 40-80 with cholelithiasis for over four weeks undergoing cholecystectomy were included. Exclusions: gallbladder cancer, chronic liver/renal disease, and pregnancy. After informed consent and pre-anesthesia evaluation, specimens were analyzed for gallbladder cancer, identifying glands lined by cuboidal or columnar cells, potentially containing mucus. Results: Age range in this study was from 40 to 80 years with mean age of 57.95 ± 9.20 years. Majority of the patients 218 (58.92%) were between 40 to 60 years of age. Out of 370 patients, 66 (17.84%) were male and 304 (82.16%) were females with male to female ratio 1:4.6. Mean duration of disease in our study was 5.85 ± 2.36 months. Mean BMI was 27.36 ± 2.94 kg/m2. In our study, incidence of carcinoma of gall bladder among patients of cholelithiasis was found in 28 (7.57%) patients. Conclusion: The research population had a 7.57% incidence of gall bladder cancer, which was mostly associated with porcelain gall bladder and chronic cholecystitis.